Peran guru PAI dalam menumbuhkan sikap toleransi antar umat beragama di SMP N 3 Batang - Rofiqotul Aini; Khofifah Khofifah (At Turots: Jurnal Pendidikan Islam, 2023)
This research is motivated by the diversity in schools, especially at SMP N 3 Batang which consists of various religions. With these differences, students are vulnerable to conflicts that have religious nuances. One of them is caused by the exclusive behavior of religious people, so that tolerance is needed. The purpose of this research is to describe the role of Islamic religious education teachers in cultivating an attitude of tolerance between religious communities at SMP N 3 Batang and to describe the obstacles and solutions in fostering this attitude of tolerance. The type of research used is descriptive qualitative with an educational sociology approach. Data collection techniques using interviews, observation, and documentation. Data analysis techniques through the process of data reduction, data presentation, and conclusions/verification. The results of the research on the role of the PAI teacher in cultivating an attitude of tolerance between religious communities in Batang 3 Public Middle School students are: fostering good relations with both Muslim and non-Muslim students, not discriminating between students, taking an emotional approach to students, incorporating tolerance material in PAI subjects, provide real examples of tolerance to students both inside and outside the classroom, create an atmosphere of peace, and establish a sense of brotherhood between teachers and students. Then the obstacles are: tolerance material that has not been spread in grades 7 and 8, non-Muslim students who have not been able to adapt because they feel they are a minority, the occurrence of miss communication between students and students and students and teachers about understanding tolerance. The solution is to enrich the insights of teachers and students by participating in training activities or seminars about tolerance, involving all students in activities and celebrations of religious holidays, providing facilities for non-Muslim students, providing good viewing recommendations or YouTube channels to students about tolerance and forming a team to anticipate and overcome obstacles or obstacles that occur related to intolerance